Integration of Technology in Arabic Language Teaching in Writing and Speaking Skills - Hajar 'Aini, Sarah; Muid, Faruq Abdul (Universitas Al-Amien Prenduan, 2024)
The study uses a mixed approach involving case studies, surveys, and field experiments to gather data and aims to explore the impact of technology integration in Arabic language teaching, in particular on student writing and speaking skills. Through case study, survey and field experiment, it was found that technologies such as language learning applications and AI-based software, make a significant positive contribution to improving student written and spoken skills. Applications like Duolingo and Grammarly have proven effective in improving student writing quality by providing instant feedback and training tailored to individual abilities. Similarly, voice recognition software and speech training apps like Google Speech-to-Text and Rosetta Stone improve student fluency and confidence in speaking. However, challenges such as gaps in access to technology in remote areas and adaptation to new technologies become major obstacles. The results of this study suggest that technology should be used as a supporting tool that complements conventional methods in Arabic language teaching, stressing the need for educational policies that support the integration of technology and the provision of adequate training for students and teacher.